Reproductive biology and diet composition of Rhynchobatus laevis (Bloch and Schneider, 1801) (Rhinopristiformes:Rhinidae) from the northern Indian Ocean - Purushottama, G. B.; Raje, Thakurdas, S. G.; Akhilesh, K. V.; Kizhakudan, Shoba Joe; Zacharia, P. U. (Indian Journal of Fisheries, 2020)
Large sized batoids particularly wedgefishes are highly vulnerable to fishing and yet very few studies have been published on their biology. The reproductive biology and feeding habit of the Rhynchobatus laevis (Bloch and Schneider, 1801) collected off the north-west coast of India, Arabian Sea, northern Indian Ocean is presented. A total of 328 individuals, in the size range from 44.0 to 290 cm total length (TL), 300 to 94000 g total weight (TW) were used for the study. The length-weight relationships were significantly different between the sexes (p